Development of Factory-Based Learning Modules in Clothing Production Units - Nurhayati Nurhayati; Abdul Hamid K; Dina Ampera (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of research and development is to develop a factory-based learning module in fashion production units in vocational schools that can be used in the classroom or for independent learning. This study was developed based on an analysis of the needs of class XI fashion students at SMK Negeri 1 Beringin. Development research using the 4D method by Thiagarajan. Has the Define, Design, Develop, and Disseminate research stages. The development process involves input from material experts, media experts, and instructional experts, as well as acceptability testing from students. The results of the research show that (1) the Teaching Factory-Based Learning Module in the Clothing Production Unit received a material expert score in the content feasibility aspect of 3.43, or 85.83% (very feasible). In the feasibility aspect of the presentation, it was 3.23, or 80.68% (feasible). Language assessment aspect: 3.54, or 88.46% (very decent). Instructional expert validation aspect: 3.32, or 82.93% (feasible). Media expert aspects of graphic feasibility are 3.68, or 91.94% (very feasible). Each validation shows that the product is suitable for use in learning. (2) The Teaching Factory Based Learning Module in the Clothing Production Unit is tested using the N-Gain Score to see the effectiveness of media use on learning outcomes. The research results showed a figure of 0.57 (medium effectiveness). Research conclusions: The Teaching Factory-Based Learning Module in the Clothing Production Unit at SMK Negeri 1 Beringin is suitable for use and is effective in improving learning outcomes.